2017
DOI: 10.1103/physrevc.96.044610
|View full text |Cite
|
Sign up to set email alerts
|

Consistent optical potential for incident and emitted low-energy α particles. II. α emission in fast-neutron-induced reactions on Zr isotopes

Abstract: Background: Challenging questions of the α-particle optical-model potential (OMP) are still pointed out by recent high-precision measurements of α-induced reaction data below the Coulomb barrier. Moreover, the reliability of a previous OMP for α-particles on nuclei within the mass number range 45≤A≤209 has been recently proved for emitted α particles as well, but only in the case of proton-induced reactions on Zn isotopes [Phys. Rev. C 91, 064611 (2015), Paper I].Purpose: Analysis of most recent (α, γ) reactio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 88 publications
(294 reference statements)
5
16
1
Order By: Relevance
“…Moreover, it was validated by the additional reaction data in the meantime [4,5] and especially 64 Zn(p, α) 61 Cu reaction cross sections [6] as well as all similar data for Cu stable isotopes [7]. Indeed, it has provided also discrepant neutron-induced α-emission but concerning an underestimation, namely for Zr isotopes [8]. However, the similar effect for A∼60 mass range has lately been accounted for by a distinct mechanism in addition to HF [3].…”
mentioning
confidence: 56%
“…Moreover, it was validated by the additional reaction data in the meantime [4,5] and especially 64 Zn(p, α) 61 Cu reaction cross sections [6] as well as all similar data for Cu stable isotopes [7]. Indeed, it has provided also discrepant neutron-induced α-emission but concerning an underestimation, namely for Zr isotopes [8]. However, the similar effect for A∼60 mass range has lately been accounted for by a distinct mechanism in addition to HF [3].…”
mentioning
confidence: 56%
“…The reliability of a previous α-particle optical-model potential (OMP) for target nuclei with mass number 45≤A≤209 [1] was also proved for α-emission in protoninduced reactions on Zn isotopes [2] (Paper I). However, its use led to underestimated predictions of the statistical Hauser-Feshbach (HF) [3] and pre-equilibrium emission (PE) [4] models for neutrons incident on Zr stable isotopes [5] (Paper II). On the other hand, it has recently been shown that this potential can also describe α-emission from excited nuclei in nucleon-induced reactions within the A∼60 range [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The so-called α-potential mystery [8] related to the account of both α-emission and absorption by an OMP, of equal interest for astrophysics and fusion technology, thus received an alternate solution. Nevertheless, its support by analysis of more data is imperative, while the case of neutrons incident on A∼90 nuclei [5] is a distinct requisite in this respect.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a former OMP [15] concerned only the α-particle emission in neutroninduced reactions, with distinct predictions from potentials for incident α particles [16]. Thus, this OMP [15] was not an earlier version of the above-mentioned ones [8,10,11], while the question on different OMPs for incident and emitted α particles [15,[17][18][19] is still unanswered.…”
Section: Introductionmentioning
confidence: 99%